2021
DOI: 10.31235/osf.io/dn43c
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

‘Stressed, uncomfortable, vulnerable, neglected’: a qualitative study of the psychological and social impact of the COVID-19 pandemic on UK frontline keyworkers.

Abstract: Aims: Non-healthcare keyworkers face distinct occupational vulnerabilities that have received little consideration within broader debates about ‘essential’ work and psychological distress during the COVID-19 pandemic. The aim of this study was therefore to explore the impact of the pandemic on the working lives and mental health and wellbeing of non-healthcare keyworkers in the UK.Methods: In-depth, semi-structured interviews were conducted with 23 participants employed in a range of non-healthcare keyworker o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
2

Relationship

4
2

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 25 publications
0
7
0
Order By: Relevance
“…Despite this, young people were more likely to have engaged in the arts than adults aged 30-59. This working age group may have faced challenges around childcare whilst working, reducing time available for leisure [19,20].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite this, young people were more likely to have engaged in the arts than adults aged 30-59. This working age group may have faced challenges around childcare whilst working, reducing time available for leisure [19,20].…”
Section: Discussionmentioning
confidence: 99%
“…Some of these activities were publicly visible, such as the proliferation of rainbow drawings amongst families in the UK to support frontline health professionals and key workers and to spread hope [23,24]. It is possible that individuals living with children had decreasing levels of arts engagement throughout the pandemic due to burnout and difficulties sustaining a balance between work, childcare, schooling, and other responsibilities [19,20]. Whilst previous studies have shown that people living in remote areas are more likely to engage in the arts [2,25], we found no associations between living area and longitudinal patterns of arts engagement.…”
Section: Discussionmentioning
confidence: 99%
“…Experienced, postgraduate, male and female, qualitative health researchers conducted all interviews (AB, AM, JD, RC, SE, TM, LB). All interviewers have previously carried out interviews about mental health and social life during the COVID-19 pandemic for other CSS research work (Aughterson et al, 2021; Burton et al, 2020; May et al, 2021).…”
Section: Methodsmentioning
confidence: 99%
“…Results showed that people globally experienced various OFCs, ranging from (1) altruistic to (2) relatively more biased. Altruistic OFCs involve worries about infecting or offending others, which are frequently expressed among the general population, non-health workers and medical professionals (May et al 2021;Fisher et al 2021;Shanafelt et al 2020). Biased OFC was also observed among the general population and medical professionals and was often complemented by obsessive distress appraisals, rumours and stigma.…”
Section: Resultsmentioning
confidence: 99%